The Effect of Initial High vs. Low FiO2 on Breathing Effort in Preterm Infants at Birth: A Randomized Controlled Trial - Dekker, Janneke; Martherus, Tessa; Lopriore, Enrico; Giera, Martin; McGillick, Erin V.; Hutten, Jeroen; van Leuteren, Ruud W.; van Kaam, Anton H.; Hooper, Stuart B.; te Pas, Arjan B. (Frontiers in Pediatrics, 2019)
Background Infants are currently stabilized at birth with initial low FiO2 which increases the risk of hypoxia and suppression of breathing in the first minutes after birth. We hypothesized that initiating stabilization at birth with a high O2 concentration, followed by titration, would improve breathing effort when compared to a low O2 concentration, followed by titration. Methods In a bi-centre randomized controlled trial, infants < 30 weeks gestation were stabilized at birth with an initial O2 concentration of 30% or 100%, followed by oxygen titration. Primary outcome was minute volume of spontaneous breathing. We also assessed tidal volumes, mean inspiratory flow rate (MIFR) and respiratory rate with a respiratory function monitor in the first 5 minutes after birth, and evaluated the duration of mask ventilation in the first 10 minutes after birth. Pulse oximetry was used to measure heart rate and SpO2 values in the first 10 minutes. Hypoxemia was defined as SpO2 <25th percentile and hyperoxia as SpO2 >95%. 8-iso-prostaglandin F2α (8iPGF2α) was measured to assess oxidative stress in cord blood and 1 and 24 hours after birth. Results 52 infants were randomized and recordings were obtained in 44 infants (100% O2-group: n=20, 30% O2-group: n=24). Minute volumes were significantly higher in the 100% O2-group (146.34 ± 112.68 mL/kg/min) compared to the 30% O2-group (74.43 ± 52.19 mL/kg/min), p=0.014. Tidal volumes and MIFR were significantly higher in the 100% O2-group, while the duration of mask ventilation given was significantly shorter. Oxygenation in the first 5 min after birth was significantly higher in infants in the 100% O2-group (85 (64 – 93)%) compared to the 30% O2-group (58 (46 – 67)%), p<0.001. The duration of hypoxemia was significantly shorter in the 100% O2-group, while the duration of hyperoxia was not different between groups. There was no difference in oxidative stress marker 8iPGF2α between the groups. Conclusion Initiating stabilization of preterm infants at birth with 100% O2 led to higher breathing effort, improved oxygenation, and a shorter duration of mask ventilation as compared to 30% O2, without increasing the risk for hyperoxia or oxidative stress.